2009
DOI: 10.1007/s12272-009-1315-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intestinal motility by the putative BKCa channel opener LDD175

Abstract: LDD175 (4-chloro-7-trifluoromethyl-10H-benzo[4,5]furo[3,2-b]indole-1-carboxylic acid) is a benzofuroindole compound characterized previously as a potent opener of the large conductance calcium activated (BK(Ca)) channels. Activators of the BK(Ca) channels are potential therapies for smooth muscle hyperactivity disorders. The present study investigates the influence of LDD175 on the mechanical activity of the ileum smooth muscle. LDD175 inhibited spontaneous contractions of the ileum in a concentration-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…Nevertheless, we can observe the uterine relaxant activity of TBIC in agonist-induced contractions via interruption of Ca 2+ influx. Previously, dela Peña et al [21] have identified that TBIC (or LDD175 in their studies) inhibited spontaneous intestinal but not myogenic contractions of the bladder [22] . A number of factors, including species difference, may have brought such inconsistency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, we can observe the uterine relaxant activity of TBIC in agonist-induced contractions via interruption of Ca 2+ influx. Previously, dela Peña et al [21] have identified that TBIC (or LDD175 in their studies) inhibited spontaneous intestinal but not myogenic contractions of the bladder [22] . A number of factors, including species difference, may have brought such inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation period was based on previous experiments showing such time was sufficient for TBIC to exert relaxant activity [20,21] . Time control experiments were also performed, as well as control experiments where vehicle was added instead of TBIC.…”
Section: Animals Isolation Of Uteri and In Vitro Contractilitymentioning
confidence: 99%
See 3 more Smart Citations